Formation of twins in AlON material and its effects on the Vickers hardness and fracture toughness. Issue 17 (1st December 2019) - Ding, Maomao; Wang, Tun; Maerz, Benjamin; Robertson, Stuart; Sun, Zehan; Fan, Lingcong; Shi, Ying; Wu, Houzheng
Abstract: Aluminum oxynitride (γ-AlON) powders were synchronously synthesized by carbothermal reduction-nitridation (CRN) and high-temperature solid state reaction (SSR) methods. Twin structures existing in γ-AlON powders and transparent AlON ceramics were investigated by systematically employing electron backscattered diffraction (EBSD) and transmission electron microscopy (TEM). It was found that the twin structures in synthetic powder and transparent ceramics exhibit quite different microstructural features; binary twin structures were widely observed in powders and ceramics, whereas the sandwich-like twin structure was produced only in transparent ceramics. High-resolution electron backscattered diffraction (HREBSD) was used to determine the residual elastic stress distributions in AlON powders and ceramics. Discrepancies in the magnitude and distribution of the residual stress between binary twins and sandwich-like twins were fully clarified. The formation of two kinds of twins in powders and ceramics was discussed in detail. The Vickers hardness and its corresponding indentation size effect (ISE) were studied in CRN-AlON and SSR-AlON ceramics. The effects of the twin structure on the Vickers hardness and fracture toughness were investigated simultaneously.